Baker's yeast: An efficient, green, and reusable biocatalyst for the one-pot synthesis of biologically important N-substituted decahydroacridine-1, 8-dione derivatives. Issue 5 (4th March 2017) - Chate, Asha V.; Sukale, Shital B.; Ugale, Reshma S.; Gill, Charansingh H.
ABSTRACT: A green approach for one-pot three-component synthesis of N -substituted decahydroacridine-1, 8-diones is offered for the first time using baker's yeast ( Saccharomyces cerevisiae ) as a biocatalyst under ultrasonication. Due to growing safety and environmental concerns, enzymatic methods were constantly investigated as an attractive alternative to toxic and nonspecific chemical approaches. This method is relatively simple, efficient, inexpensive, and environment-friendly. The catalyst was recovered and reused and also the recyclability of baker's yeast resulted in excellent yields of products without loss of any catalytic activity. GRAPHICAL ABSTRACT: